ANALYSIS OF QUANTITATIVE INDICATORS OF THE TREATMENT OF TEETH CARIES IN HEALTH CARE INSTITUTIONS OF THE KIROVOGRAD REGION - O.A. Udod; S.I. Dramaretska; O.B. Roman; V.O. Voloshyn (Український стоматологічний альманах, 2023)
Relevance. Reforming the health care of the country affected some indicators of dental care for the population.